Agreement on trade and investment between CARICOM and Venezuela (Trinidad Express Newspapers Ltd. Port of SpainTT, 1993)
Provides the text of the Agreement as well as other related items.
Supplement to Caribbean Affairs V.6. No. 1 Jan-Mar 1993.